Utilizing Citizen Contribution to Track Cosmic Material Entry into Earth's Atmosphere: Insights from Mexico - Arturo Cuevas Muñóz; Andrea Monserrat Gallegos Flores; María Guadalupe Cordero Tercero (Geofísica Internacional)
In this paper, the importance of information posted on social networks in the study of meteoroid entry into the Earth’s atmosphere is shown. This kind of networks work thanks to the information shared by many people, which is stored on different servers. Using these reservoirs, we identified 24 such events between April 2013 and November 2023, most of which were not recorded even by satellites such as GOES or other U.S. government sensors. Furthermore, from the collected information we estimated the trajectory of five meteoroids and the mean angular velocity of three of these.